(untitled) (Journal of Partial Differential Equations, 2000)
With the use of Hölder Zygmund space techniques, local regular solutions to the Navier-Stokes equations in R^n are shown to exist when the initial data are in the space a|(-Δ)^-β/2a ∈ C^0(R^n)^n(0 < β < 1)